PENGARUH WORD OF MOUTH DAN SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN PADA JASA EKSPEDISI J&T EKSPRESS - Novitasari, Meisha Yana; Andayani, M.M, Dra. Sri; Pudjianto, M.M, Drs. Agung (Research Journal of Social Science and Economics, 2025)
ABSTRACT The business world is currently growing, especially in the field of online shops, which can be seen from the large number of goods that must be delivered by courier services to online shop consumers. J&T Express expedition services can attract consumers to use their services again and recommend potential customers to use J&T Express expedition services because the service quality is very good. Therefore, researchers try to provide a detailed explanation of how service quality and word of mouth affect customer satisfaction with J&T Ekspress expedition services. This study used a quantitative method by distributing questionnaires. The sample consists of 96 respondents. This study found that Word Of Mouth and Quality of Service factors had a significant influence on the level of customer satisfaction with J&T Ekspress expedition services. Keywords: Word Of Mouth, Service Quality, Consumer Satisfaction